CHARACTERISTICS OF SELF-ORGANIZATION IN ADOLESCENT STUDENT-ATHLETES - SAPARBOYEV , Mirzabek («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
This article presents the results of an assessment of the development of self-organization components in adolescent student athletes studying in comprehensive schools. The conducted research demonstrated how these components manifest themselves at various levels of development (average, above average, below average). It was revealed that half of the student athletes surveyed had only an average level of self-organization skills. This underscores the urgent need for targeted pedagogical interventions for this category of students to improve their self-organization.